Estudio numérico del comportamiento estructural del perfil del álabe de un rotor tipo Savonius implementando una geometría multielemento - Gallo Jaramillo, Luis Antonio; Chica Arrieta, Edwin Lenin; Flórez Serrano, Elkin Gregorio (Ingeniería, 2023)
Context: This study evaluates the structural stability of a Savonius-type rotor by implementing a multiblade profile, with the purpose of reducing the resistance to movement and consequently improving aerodynamic performance. The rotor with the profile under study was compared against rotors with conventional semicircular and split Bach profiles. Method: The fluid-structure interaction was analyzed by numerically simulating the three rotors, and the state of stresses and deformations was determined under a normal operating regime. The rotors were assigned the same construction material, and they were studied under the same parameters and models of fluid dynamics and computational mechanics via the ANSYS software. Results: The results obtained showed a better structural behavior in the rotor with the multiblade configuration, reducing the maximum equivalent stress by 59,10 and 42,87% and the deformations by 47,40 and 33,59% with respect to the rotors with the conventional semicircular and split Bach profiles, respectively. Conclusions: The multiblade configuration allows for greater aerodynamic and structural performance while preserving the construction and operation simplicity that characterize Savonius-type rotors.